KEMAMPUAN MENULIS TEKS DRAMA MELALUI TEKNIK TRANSFORMASI - Fransisca S.O. Dedi; Dian Permanasari; Riska Alfiawati (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2021)
Drama learning material in Indonesian language lessons is one part of the literary aspect. The ultimate goal of learning is that students are required to be able to compose drama texts in their own style. This certainly requires a high understanding for students to be able to analyze the structure, characteristics and elements that are specifically contained in a drama. The purpose of this study is to describe how the ability to write drama texts in class VIII students of SMP Negeri 32 Bandar Lampung. The method used in this study is a quantitative descriptive approach. The results of this study can be described as follows. The ability of Class VIII students of SMP Negeri 32 Bandar Lampung in writing drama texts is categorized as sufficient.